Overcoming Reproductive and Psychological Concerns of Breast Cancer Survivors: A Randomized Controlled Trial - Samira Barjasteh; Farnaz Farnam; Aymen Elsous; Saharnaz Nedjat; Saeid Razavi Dizaji; Zohreh Khakbazan (Tehran University of Medical Sciences, 2022)
Objective: After developing breast cancer, women experience changes in their sexuality, femininity, and fertility. These changes lead to poor mental health and increased psychological stress. Therefore, this study aimed to investigate the effects of Good Enough Sex (GES)-based, couple-centered group counseling on reproductive and sexual concerns of breast cancer survivors. Materials and methods: This was a quantitative randomized controlled clinical trial (RCT) conducted at Omid Hospital, West Azerbaijan, Urmia, Iran from March 2018 to October 2020. After completing the informed consent forms, 100 women were assigned to the intervention and control groups (50 individuals per group) using a randomized block design. The intervention included four 90-120-minute sexual counseling sessions with 2 and 3 month follow-ups. The data were collected using the socio-demographic and clinical characteristics, the Persian version of Depression, Anxiety and Stress Scale (DASS-21), Reproductive Concerns after Cancer (RCAC) scale, and Female Sexual Function Index adaptation for Breast Cancer patients (FSFI-BC). Data were collected, from control and intervention groups, at three intervals; before, besides two months and three months post intervention, then were analyzed in SPSS 20 using descriptive and repeated measures analysis of variance (ANOVA) test. Results: Significant reduction in the mean score of DASS-21, RCAC and improvement of FSFI-BC is reported between the intervention and control groups in favor of intervention group (P<0.001). However, no significant differences are observed within intervention group over two- and three-months post intervention (P > 0.05). Conclusion: The designed Good Enough Sex (GES)-based, couple-centered group counseling effectively reduced reproductive and sexual concerns of females' breast cancer survivors. Therefore, these training and counseling programs can be organized by relevant service centers to promote the reproductive health of women with breast cancer.